Game Edukasi Ilmu Pengetahuan Sosial (IPS) Berbasis Android menggunakan Metode R&D 4D di SMP Negeri 2 Rawalo - Annas Ridwan Pangestu; Sigit Sugiyanto; Tito Pinandita; Dimara Kusuma Hakim (Sekawan Institut, 2026)
Technological advancements have had a significant impact on the world of education, particularly in accelerating and simplifying the learning process for Social Studies (IPS) courses. This study aims to design an Android-based educational game for 9th-grade students at SMP Negeri 2 Rawalo using the Research and Development (R&D) method and the 4D model (define, design, develop, disseminate). This game was designed using the Construct 3 application and named “Society in A Game: Game of Social Changes and Digital Economy Growth.” The study involved 20 students, and the research utilized pre-tests and post-tests to measure improvements in learning outcomes as well as an application evaluation test using the System Usability Scale (SUS) based on a 1–4 Likert scale. The average pre-test score of 57.8 increased to 77.6 on the post-test, representing a 34.2% increase. Additionally, the average SUS score of 74.5 falls into the “Acceptable” category. The research results indicate that Android-based educational games can serve as an interactive learning medium while introducing the use of technology in the field of education.